Die Minoischen Villen Kretas Ein Vergleich spätbronzezeitlicher Fund- und Siedlungsplätze - Adlung, Sebastian (Hamburg University Press, 2020)
The Minoan palaces and villas often give the impression of a late bronze age culture which was characterized by elitist societies and mysterious cults. The numerous known Bronze Age settlement sites and their rich finds in different regions of Crete illustrate varying settlement developments. This study presents a comprehensive overview of found materials, building features and site conditions of 23 Minoan villas in Crete. The analysis is decisively extended by including the geographical conditions of the surroundings and by comparing the Minoan villas with other late bronze age find and settlement sites in Crete. The investigation offers perspectives to review established interpretations of late bronze age settlement conditions of Minoan Crete.